Policy Analysis of the Sports Achievement Development Program in Papua After the XX National Sports Week (PON) Based on the Perception of KONI Papua - Caro, Carolus Wasa; Rahayu, Tandiyo; Setijono, Hari; Hartono, Mugiyo; Yambedoan, Thadius (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2024)
Analyzing the policies for the achievement sports development program in Papua after the XX National Sports Week (PON) based on KONI Papua's perception is something that must be done because achievement sports development must be carried out in a planned, systematic, measurable and sustainable manner. This research aims to analyze the policy of the achievement sports development program in Papua after the XX PON based on the perception of KONI Papua. Using qualitative methods with interview, observation and documentation data collection techniques. With the policy analysis methodology used in problem solving: problem formulation, forecasting, recommendations, monitoring and evaluation. The participants were the Indonesian National Sports Committee (KONI) Papua, numbering 1 person.In generalpolicy for sports achievement development programs in Papua after the national sports week(PON) XX based on KONI Papua's perceptionnot yet integrated well due to internal factors in sports coaching such as the very limited sports coaching budget.